Nocardiosis in the Tropical Northern Territory of Australia, 1997–2014. (8th December 2016) - McGuinness, Sarah L.; Whiting, Sarah E.; Baird, Rob; Currie, Bart J.; Ralph, Anna P.; Anstey, Nicholas M.; Price, Ric N.; Davis, Joshua S.; Tong, Steven Y. C.
Abstract: Background: Nocardia is an opportunistic pathogen that can cause life-threatening disease. We aimed to characterize the epidemiological, microbiological, and clinical features of nocardiosis in the tropical north of Australia. Methods: We conducted a retrospective cohort study of nocardiosis diagnosed between 1997 and 2014. Population-based incidences were calculated using district population data. Results: Clinically significant nocardiosis was identified in 61 patients. The unadjusted population-based annual incidence of nocardiosis was 2.02 (95% confidence interval [CI], 1.55–2.60) per 100000 people and was 1.7 (95% CI, .96–2.90) fold higher in Indigenous compared with non-Indigenous persons ( P = .027). Of 61 patients, 47 (77%) had chronic lung disease, diabetes, and/or hazardous alcohol consumption; 22 (36%) were immunocompromised; and 8 (13%) had no identified comorbidities. Disease presentations included pulmonary (69%; 42 of 61), cutaneous (13%; 8 of 61), and disseminated nocardiosis (15%; 9 of 61). The most commonly identified species were Nocardia asteroides and Nocardia cyriacigeorgica (each 11%). Linezolid was the only antimicrobial to which isolates were universally susceptible; 89% (48 of 54), 60% (32 of 53), and 48% (26 of 54) of isolates were susceptible to trimethoprim-sulfamethoxazole, ceftriaxone, and imipenem, respectively. Eighteen patients (30%) required intensive care unit (ICU) admission, and 1-year mortality was 31%. Conclusions: The incidence of nocardiosis in tropical Australia is amongst the highest reported globally. Nocardiosis occurs in both immunocompromised and immunocompetent hosts, and it is associated with high rates of ICU admission, 1-year mortality, and resistance to commonly recommended antimicrobials. Diagnosis should be considered in patients with consistent clinical features, particularly if they are Indigenous or have chronic lung disease.